PKA Signaling in ABCA1 Function: A Role in Modulation of Cholesterol Efflux and Macrophage Inflammation - Ma, Loretta T. K. (Université d'Ottawa / University of Ottawa, 2013)
Formation of lipid-laden macrophage foam cells and inflammation are the central components in the initiation and progression of atherosclerosis. ABCA1 is well established as an anti-atherogenic factor that facilitates cellular cholesterol and phospholipid efflux, promotes reverse cholesterol transport, and suppresses pro-inflammatory cytokine secretion. Through these functions, ABCA1 is capable of reducing the lipid burden in atherosclerotic plaque. PKA signaling is an integral factor in promoting many anti-atherogenic functions of ABCA1; however, mechanistic aspects of PKA signaling associated with ABCA1 remain poorly defined. Thus, the first part of this study investigates the involvement of spatially regulated PKA signaling in ABCA1 activities through the use of st-Ht31, a PKA de-anchoring peptide. It appears that de-anchoring PKA robustly increases ABCA1-mediated microparticle release, one of the cholesterol efflux pathways of ABCA1, and reverses macrophage foam cell formation. These results highlight the significance of subcellular compartmentalization of PKA signaling in ABCA1 functions and present PKA de-anchoring as a potential therapeutic strategy for atherosclerotic lesion regression. The second part of this study provides evidence that ABCA1 activates PKA and promotes the secretion of anti-inflammatory IL-10, a cytokine crucial for inflammation resolution. Furthermore, we provide evidence that this elevated PKA activity is the underlying mechanism in which macrophage ABCA1 promotes M2-like inflammatory response. Our results also suggest that ABCA1 activates PKA by regulating cholesterol, which poises macrophages towards an anti-inflammatory or M2-activated phenotype. Collectively, we demonstrate that PKA signaling plays a crucial multifactorial role in anti-atherogenic functions of ABCA1.
Keywords: ABCA1; PKA; cholesterol; anti-inflammatory; macrophage; IL-10; A-kinase anchoring protein